INTEGRATING FINANCIAL LITERACY INTO GEN Z'S PAYLATER CONSUMPTION AND FINANCIAL WELL-BEING: A CONCEPTUAL PAPER - Asterina Anggraini; Annisa Wardhani; Nuraeni Hadiati Farhani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This paper discusses how using Buy Now Pay Later (BNPL) affects the financial well-being of Generation Z in Indonesia. This comes at a time when digital financial services are rapidly growing and young consumers are spending more. The study aims to create a framework that explains the connection between PayLater usage, impulsive buying, financial literacy, and financial well-being. It uses a conceptual and explanatory method, including a thorough review of recent studies on fintech behavior, behavioral finance, and digital consumption trends. The findings show that using PayLater can lead to more impulsive buying. This is due to deferred payment options, the convenience of digital transactions, and strong online promotions. These factors may harm financial well-being by increasing stress, leading to high digital debt, weak spending habits, and reduced saving ability. However, financial literacy is seen as a protective factor. It can help lessen the negative impact of PayLater by promoting smarter financial choices and better money management among Generation Z. This paper adds to the understanding of fintech and behavioral finance in the context of Indonesia’s digital economy.